2020
DOI: 10.1515/nanoph-2020-0156
|View full text |Cite
|
Sign up to set email alerts
|

Multipolar second-harmonic generation from high-Q quasi-BIC states in subwavelength resonators

Abstract: We put forward the multipolar model which captures the physics behind linear and nonlinear response driven by high-quality (high-Q) supercavity modes in subwavelength particles. We show that the formation of such trapped states associated with bound states in the continuum (quasi-BIC) can be understood through multipolar transformations of coupled leaky modes. The quasi-BIC state appears with increasing the order of the dominating multipole, where dipolar losses are completely suppressed. The efficient optical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 47 publications
0
46
0
Order By: Relevance
“…(d) is adapted with permission. [ 41 ] Copyright 2020, Irina Volkovskaya et al, published by De Gruyter, Berlin/Boston. e–g) Evolution of the Q‐factors (top row) and the power (middle row) radiated from all non‐negligible multipoles for the supermodes of order ν p ∈ {0, 1, 2} that for p ‐polarized light correspond to the magnetic dipole (MD), electric dipole (ED), and electric quadrupole (EQ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(d) is adapted with permission. [ 41 ] Copyright 2020, Irina Volkovskaya et al, published by De Gruyter, Berlin/Boston. e–g) Evolution of the Q‐factors (top row) and the power (middle row) radiated from all non‐negligible multipoles for the supermodes of order ν p ∈ {0, 1, 2} that for p ‐polarized light correspond to the magnetic dipole (MD), electric dipole (ED), and electric quadrupole (EQ).…”
Section: Introductionmentioning
confidence: 99%
“…Yet another important application of the multipole analysis approach is the decomposition of the incident radiation depicted in Figure 1d in terms of the vector spherical harmonics. [ 41 ] The concept is applied to get the values of the incident multipolar content of the azimuthally polarized cylindrical vector beam, and in particular, its magnetic dipolar and octupolar components. The analysis is then applied to the experimental data published in ref.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been demonstrated that a single dielectric structure can support a high-Q cavity mode, realized in several specific examples [also referred to as quasi-BIC (QBIC)]. [14][15][16][17][18][19][20][21] Despite that, it is still necessary to develop a robust approach of finding out all high-Q modes in dielectric cavities of arbitrary shapes, including structures with a rectangular cross section for both two-dimensional (2D) and threedimensional (3D) cases (i.e., rectangular wire, cylinder with finite thickness, and cuboid) since they can be easily fabricated with current nanofabrication technology.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple approaches attaining this optical localization can be found in the literature as devices based on photonic crystals [93], plasmonic structures [149], ring resonators [150] or high-index dielectric nanoparticles [57], between others. Concerning the last ones, high-index dielectric nanoparticles can exhibit strong near-field confinement and tailorable field distributions in the subwavelength regime [151] due to the simultaneous support of both electric and magnetic Mie resonances [147]. However, a limiting factor of these dielectric systems can be found in the low optical quality factor of their resonances [58].…”
Section: Quasi-bic Modes In High-index Disksmentioning
confidence: 99%